The costs of implementing and sustaining a trauma and mental health screening tool in a state child welfare system. (July 2020) - Butcher, Rebecca L.; Jankowski, M. Kay; Slade, Eric D.
Highlights: The costs to implement trauma screening in child welfare are largely unknown. Child welfare staff in NH were trained to use a new screening tool on children 0–18 years. Implementation costs were estimated at 1, 213 per caseworker (641 in direct costs). The per-child costs of screening and associated activities were 74/screen. The methods will be useful for others interested in expanding trauma-informed care. Abstract: Little information is available regarding the financial and non-financial costs of implementing and sustaining universal trauma and mental health screening in state child welfare systems. A cost analysis was conducted as part of a 5-year, federally funded statewide demonstration project to install universal trauma screening in one state's child welfare system. The project implemented a battery of validated instruments that varied by age of the child (0–18) to measure trauma exposure, post-traumatic symptoms and child well-being. All adjudicated children and youth involved in the state child welfare system are targeted for initial screening within the first 60 days, and then every subsequent 6 months while in care. The cost of administering the screening tool and related post-screening activities was estimated to be 74 per screen in 2016 dollars. Overall, implementation and maintenance costs were estimated at 1213/trained caseworker, including both direct and indirect costs. Costs to sustain screening activity past the grant period were also calculated. While the grant funding provided more dedicated resources than states may typically have for implementing a new screening initiative, most of the cost-related screening processes reported here, such as planning (e.g., choosing measures, determining workflow) and implementation (workforce training, programming a web-based interface) would be necessary for any state or territory wanting to install universal screening. With growing interest in trauma-informed screening and prevention in child welfare, it is critical to understand and determine the financial costs of screening.